2004
DOI: 10.1089/jwh.2004.13.1127
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Issues Associated with Knowledge of and Access to Topical Microbicides

Abstract: Consideration of the adolescent-specific issues in the design of microbicides and marketing strategies may be crucial for adolescent adoption of this female-controlled method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Similar to existing research [7,11], young women's preferences were sensitive to side effects, contraceptive properties, and timing of application. Specifically, adolescent women reported an ordered preference for a microbicide with no side effects, having contraceptive properties, applied 10 minutes postcoitally, and protecting against STI rather than HIV.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Similar to existing research [7,11], young women's preferences were sensitive to side effects, contraceptive properties, and timing of application. Specifically, adolescent women reported an ordered preference for a microbicide with no side effects, having contraceptive properties, applied 10 minutes postcoitally, and protecting against STI rather than HIV.…”
Section: Discussionsupporting
confidence: 64%
“…Extant microbicide acceptability research with young women has suggested that contraceptive and disease prevention properties, timing of use, and associated side effects are important characteristics [7]. The findings suggest that young women generally prefer both pregnancy and disease prevention in a single product and insertion with an applicator up to 8 hours in advance [8].…”
mentioning
confidence: 99%
See 3 more Smart Citations